Pattern of Head Injury and Recovery in First and Second Rider in Motor Bike Accidents - Yasir Shehzad,. Ayesha Arshad, Nadeem Akhter (Journal of Rawalpindi Medical College, 2017)
To compare the rate and pattern of head injury sustained by the first vs. second rider and mortality rate and functional outcome of the two groups. Methods: In this cross sectional study all adult patients presenting with head injury resulting from a motorcycle accident, during the study period were enrolled.Proforma’s were filled by the on-duty doctor, including the demographic details, details regarding helmet and first or second rider, neurological status, additional injuries and radiological pattern of injury. These patients were divided into two groups: Group-1 (First riders) and Group-2 (Second riders) and both groups were compared for the above details, and followed. All patients received the standard treatment for their respective injuries and the two groups were compared for the mortality and neurological and functional outcome, assessed by using the Extended Glascow Outcome Scale. (EGOS). Results: A total of 360 patients were included in the study. Of these,65% patients were in group-1 and 35% were in group-2. The mean age of the two groups was 27.86 and 30.12 years respectively. All patients in group-1 were males while 61.9% in group-2 were males. Majority of the riders in both groups were not wearing helmets at the time of accident. Major injury in both the groups was facial injury but the frequency of facial injury was significantly higher in group-1 as compared to group-2 i.e. 20.5% vs. 11.9% (p = 0.040). CT brain showed normal scan in 15.4% patients in group-1 and in 2.4% patients in group-2. In group-1, CT brain showed highest frequency of traumatic brain contusions (24.4%) followed by Extradural hematomas (14.1%) and cranium fracture (12.8%). In group-2, CT brain showed highest frequency of traumatic brain contusions (35.7%) followed by cranium fracture (16.7%), ASDH (9.5%) and TSAH (9.5%). Complete recovery was significantly higher in group-1 as compared to group-2 (p = 0.011). Conclusion: In motor bike riding head injury is a potential threat not only to the 1st rider but also to the 2nd rider as well. By using helmets head injury, which is fatal in most of the instances, can be avoided.